A questionnaire based study on the knowledge, attitude and the practices of pharmacovigilance among the postgraduate students at a tertiary care hospital in south India - Kumar, Chiranjeevi Uday; Rao, G. Harijagannadha; Vasavi, G. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Adverse drug reactions (ADRs) are common cause of morbidity in the practice of medicine. Pharmacovigilance is the science of detection, assessment and understanding and prevention of adverse effects or any drug related problems. Post graduates are perhaps the first to notice ADRs in outpatient/inpatient setup as they spend most of the time bedside. Thus, this study was conducted to assess the knowledge, attitude and practices (KAP) of postgraduates about Pharmacovigilance. Methods: A prevalidated and pretested questionnaire with 20 questions related to KAP of pharmacovigilance is administered to postgraduate students after obtaining their consent. All the completed and returned questionnaires were analysed for results using appropriate statistics. Results: 180 pretested questionnaires were distributed among postgraduates out of which, 122 were returned from postgraduates of all major medical and surgical allied departments. 90.2 % defined pharmacovigilance correctly, 83.6% thought reporting ADRs is a professional obligation, while only 65.6% knew regarding the existence of national pharmacovigilance program. 58.4% have experienced ADRs, of which only 24.6% reported ADR to pharmacovigilance centre. Major reasons for under reporting are lack of time to report and difficulty to decide whether ADR has occurred or not. Conclusions: In this study, the knowledge and attitude related to Pharmacovigilance is good amongst postgraduates, but practical implementation in reporting of ADRs is poor. Sensitization programs on pharmacovigilance practice in tertiary care hospitals and regular review meetings to ensure ADR reporting to pharmacovigilance centre will strengthen the health care setup.